Monitoring Sun Tracking Solar Panel Statis Secara Real-Time Berbasis Website - Hanifiyah Darna Fidya Amaral; Santoso, Asfari Hariz; Harijanto , Priya Surya; Wibisono, Krisna Adi (Elposys: Jurnal Sistem Kelistrikan, 2023)
The ability of solar panels to absorb energy depends on environmental conditions. Therefore, the power generated will fluctuate. Web-Based Real-Time Solar Panel Monitoring Design Research can facilitate monitoring the condition of solar panels so as to speed up action when there is a problem with solar panels with the monitoring system sent to users. The component used is NodeMCU ESP32 as a connecting device between solar panels and the internet. The measurement data of the current and voltage sensors installed on the solar panels is sent through an internet connection to the web server. The web server will receive the data and display real-time solar panel current and voltage information through a web interface that can be accessed by users. The test was carried out by taking current and voltage data on static solar panels and solar trackers for 11 hours at 07.00 – 17.00 WIB. Based on the measurement results, a total power of 16.04 Wh without a solar tracker (static) and 17.43 Wh with a solar tracker was obtained. The percentage of increase in current and power between static solar panels and solar trackers is 7.22% and 3.05%.